Raised Plasma Homocysteine: An Emerging Risk Factor for Ischaemic Heart Disease (TAJ: Journal of Teachers Association, 2009)
Only one half to two thirds of atherosclerotic vascular diseases can be explained by classical risk factors like smoking, diabetes mellitus, hypertension, dyslipidaemia, family history of premature atherosclerotic vascular diseases, physical inactivity, obesity etc. Some other variables appear to contribute to the development of atherosclerotic vascular diseases which include estrogen deficiency, lipoprotein (a), plasma fibrinogen, plasminogen-activator inhibitor type I, endogenous tissue plasminogen activator (tPA), C-reactive protein and homocysteine. Over the last several years, investigators undertook extensive research work, in home and abroad, to determine the contribution of plasma homocysteine in the pathogenesis of atherosclerotic vascular diseases. So far the research work indicates, raised plasma homocysteine appears to be a potential risk factor for ischaemic heart disease.   doi: 10.3329/taj.v19i2.3158 TAJ 2006; 19(2): 87-93